Assessing the Bank Stability Nexus: Islamic Bank Competition in the Indonesian Financial Landscape - Setiawan, Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The existence of Islamic banks in Indonesia has contributed to the competition in the banking world. Apart from competing with fellow Islamic banks, Islamic banks must also compete with conventional banks which are much larger and experienced. The purpose of this research is to explore the influence of Islamic bank competition on financial stability and the differences among Islamic banks in Indonesia. This research is quantitative research with an associative approach using secondary data. The sample of Islamic banks is 11 Islamic commercial banks registered with the Financial Services Authority (OJK). The results of the study show that in model 1 it is found that Islamic bank competition has a significant effect on Islamic bank stability, and in the second model it is found that Islamic bank competition has a significant effect on Islamic bank stability with moderation in Islamic bank size. Competition motivates Islamic banks to enhance operational efficiency through cost reduction, increased productivity, and the adoption of advanced technology. This efficiency strengthens their financial performance and resilience to economic shocks.